Collaborative Efforts for Spinocerebellar Ataxia Research in the United States: CRC-SCA and READISCA - Lin, Chih-Chun; Ashizawa, Tetsuo; Kuo, Sheng-Han (Frontiers in Neurology, 2020)
Spinocerebellar ataxias are progressive neurodegenerative disorders primarily affecting the cerebellum. Although the first disease-causing gene was identified nearly 30 years ago, there is no known cure to date, and only few options exist for symptomatic treatment with modest effects. Recently developed tools in molecular biology such as CRISPR/Cas9 and antisense oligonucleotides can directly act on the disease mechanisms at the genomic or RNA level in disease models. In a nutshell, we are finally just one step away from clinical trials with therapies targeting the underlying genetic cause. However, we still face the challenges for rare neurodegenerative diseases: difficulty in obtaining large cohort size for sufficient statistical power and the need for biomarkers and clinical outcome assessments (COA) with adequate sensitivity to reflect progression or treatment responses. To overcome these obstacles, ataxia experts form research networks for clinical trial readiness. In this review, we retrace our steps of the collaborative efforts among ataxia researchers in the United States over the years to study and treat these relentless disorders and the future directions of such research networks.